Effect of Different Remelting Parameters on Slag Temperature and Energy Consumption during ESR - David, D. (Iron and Steel Institute of Japan, 2022)
Energy consumption is a vital aspect in the production of high quality materials by using electro slag remelting as a refining method. The electrical conductivity and the melting point of the slag, determined by the slag composition, as well as the fill ratio, the amount of slag and the melt rate have as significant influence. Several of these factors as well as a new method to measure the slag surface temperature with a two-color pyrometer were investigated in laboratory scale remelting trials. Two different slags with an average and a low electrical conductivity were used. While there is only a small impact of the slag cap height and the melt rate, the slag composition showed a strong effect, both on the slag surface temperature as well as on the specific energy consumption. Additional investigations confirmed that the effect of the slag composition on the amount and compositions of non-metallic inclusions, respectively the cleanliness level of the steel after remelting is rather minor. The results suggest possibilities for easily applicable, improved process parameters, which can combine high product quality with significantly reduced energy consumption © 2022 Iron and Steel Institute of Japan. All rights reserved.